Digital clock drawing test reflects visuospatial ability of older drivers - Yamauchi, Satsuki; Kawano, Naoko; Shimazaki, Kan; Shinkai, Hiroko; Kojima, Masae; Shinohara, Kazumitsu; Aoki, Hirofumi (Frontiers in Psychology, 2024)
Objectives To keep older drivers safe, it is necessary to assess their fitness to drive. We developed a touch screen-based digital Clock Drawing Test (dCDT) and examined the relationship between the dCDT scores and on-road driving performance of older drivers in a community-setting. Methods One hundred and forty-one community-dwelling older drivers (range; 64–88 years old) who participated in this study were included in the analysis. Participants completed the dCDT, the Mini-Mental State Examination-Japanese (MMSE-J), and an on-road driving assessment. We examined the relationship between dCDT scores using the method by Rouleau et al. (maximum 10 points) and the on-road driving performance based on a driving assessment system originally developed by Nagoya University. Results Multiple regression analyses showed that errors in the driving test were associated with dCDT score for the items “confirmation,” “turning left” and “maintains driving lane position”. Discussion This study confirmed the relationship between the dCDT score and driving errors, such as confirmation, turning left and maintaining driving lane position. The increase in these errors indicates a decline in visuospatial ability while driving. The dCDT score may reflect older drivers’ visuospatial abilities while driving.